18. FEEDBACK OF STUDENTS OF PREVENTIVE MEDICINE DOCTORS OF HANOI MEDICAL UNIVERSITY ON CLINICAL LEARNING AT BACH MAI HOSPITAL IN 2022-2023 (Vietnam Journal of Community Medicine, 2023)
Introduction: Clinical learning is one of the indispensable modules in the medical training program. Thanks to clinical skills, medical students can integrate their knowledge to make correct and effective decisions in treating and caring for patients. Objective: Describe the feedback of students majoring in Preventive Medicine at Hanoi Medical University about the clinical learning process at Bach Mai Hospital and some related factors in the 2022-2023 school year.Research method: Cross-sectional description of 280 Preventive Medicine students at Hanoi Medical University. The study used self-developed and designed questionnaires on REDcap software. The survey link was sent to classes for students to complete the questionnaires.Results: 100% of student feedback on lecture content and teaching methods did not reach the “agree” level (4 points). The average score on lecture content ranges from 3.67 to 3.87 points. The average score on teaching methods ranges from 3.52 to 3.74 points. The average score for lecturers’ responsibility and pedagogical style ranges from 3.63 to 3.77 points. Regarding the evaluation test, feedback scores ranged from 3.5 to 3.68. The factor related to a good response rate is students with good academic performance (OR = 0.28, 95% CI: 0.08-0.94).Conclusion: The training department needs to increase communication on program management and operations with the Department to ensure that lecturers arrange their lecture schedules according to the school’s prescribed teaching time.
Keywords: Clinical studies, preventive medicine doctor, Bach Mai Hospital.